Simulation study on CCD tomography system for ruby stone optical properties - Syarfa Najihah, Raisin; Juliza, Jamaludin; Irneza, Ismail; Yasmin, Abdul Wahab; Ruzairi, Abdul Rahim; Mus'ab, Sahrim; Sharma Rao, Balakrishnan; Wan Zakiah, Wan Ismail; Fatinah, Mohd Rahalim; Farah Aina, Jamal Mohamad; Nurul Arina Hazwani, Samsu Zaini (Malaysian Society for Computed Tomography and Imaging (MyCT), 2021)
Ninety percent of the ruby stones available worldwide come from Myanmar. Malaysia is known to be one of the countries that have been importing ruby stones for precious stone industries, manufacturing industries, medical and dentistry applications. There are several gemology tools which are used to investigate the grading of ruby stones such as loop, microscope, and dichroscope. Nevertheless, these tools are highly dependable on human visual assessment and require years of experience that may lead to error since ruby stone quality is evaluated based on its clarity and transparency. Hence, this paper addresses a simulation study on the optical properties of ruby stones via Charge-Coupled Device (CCD) Tomography approach. This paper indicates the capability of CCD and tomography system to analyze the ruby stone optical properties through image reconstruction based on the previous research. Linear Back Projection (LBP) algorithm will be used to construct two-dimensional image reconstruction of varieties ruby stones. From these image reconstructions, the transparency and blemishes of ruby stones can be analyzed.